The role of long non-coding RNAs in genome formatting and expression - Angrand, Pierre-Olivier; Vennin, Constance; Le Bourhis, Xuefen; Adriaenssens, Eric (Frontiers in Genetics, 2015)
Long non-coding RNAs (lncRNAs) are transcripts without protein-coding potential but having a pivotal role in numerous biological functions. Long non-coding RNAs act as regulators at different levels of gene expression including chromatin organization, transcriptional regulation, and post-transcriptional control. Misregulation of lncRNAs expression has been found to be associated to cancer and other human disorders. Here, we review the different types of lncRNAs, their mechanisms of action on genome formatting and expression and emphasized on the multifaceted action of the H19 lncRNA.